The Andes Cordillera. Part IV: spatio‐temporal freshwater run‐off distribution to adjacent seas (1979–2014). (4th November 2016) - Mernild, Sebastian H.; Liston, Glen E.; Hiemstra, Christopher; Beckerman, Andrew P.; Yde, Jacob C.; McPhee, James
ABSTRACT: The spatio‐temporal freshwater river run‐off pattern from individual basins, including their run‐off magnitude and change (1979/1980–2013/2014), was simulated for the Andes Cordillera west of the Continental Divide in an effort to understand run‐off variations and freshwater fluxes to adjacent fjords, Pacific Ocean, and Drake Passage. The modelling tool SnowModel/HydroFlow was applied to simulate river run‐off at 3‐h intervals to resolve the diurnal cycle and at 4‐km horizontal grid increments using atmospheric forcing from NASA Modern‐Era Retrospective Analysis for Research and Applications (MERRA) data sets. Simulated river run‐off hydrographs were verified against independent observed hydrographs. For the domain, 86% of the simulated run‐off originated from rain, 12% from snowmelt, and 2% from ice melt, whereas for Chile, the water‐source distribution was 69, 24, and 7%, respectively. Along the Andes Cordillera, the 35‐year mean basin outlet‐specific run‐off (L s −1 km −2 ) showed a characteristic regional hourglass shape pattern with highest run‐off in both Colombia and Ecuador and in Patagonia, and lowest run‐off in the Atacama Desert area. An Empirical Orthogonal Function analysis identified correlations between the spatio‐temporal pattern of run‐off and flux to the El Niño Southern Oscillation Index and to the Pacific Decadal Oscillation.